Students Age at which EFL is Introduced in Schools and Educational Outcomes - Chuzaimah Dahlan Diem (TEFLIN, 2004)
This study tries to see the relationship between the age at which EFL is introduced in public schools and educational processes and outcomes. A survey involving 229 students from elementary and junior high schools in Palembang is conducted. The population consists of those who have never taken extra non-formal English courses. These students are given the same English tests comprising mostly vocabulary and reading comprehension followed by a small portion of grammar. It is hypothesized that those who start learning English earlier have better achievement. Curriculum, intensity of instruction, teacher education level, years of ELT experience are considered in the analysis, in addition to class size, students SES and gender. Stepwise regression analysis is applied to identify which variable contributes to students outcomes. The results show there is no correlation between age alone and the students EFL achievement. However, negative significant correlation is found between the students achievement and teacher education level and also between the students achievement and SES. Finally, some implications of research for theory, policy, and practice are suggested.